Isolation and partial characterization of a myotoxin from Bothrops atrox snake venom (Ophidia: Viperidae) - Huatuco, Sergio (2004)
A myotoxin from Bothrops atrox snake venom was purified by cationic exchange on CM-Sephadex C-50 with 0,05M ammonium acetate pH 7. The myotoxin is a basic protein and by gel filtration and PAGE-SDS was demonstrated that protein has a molecular weight of 27 kDa and two polipeptides chain of 14 kDa each one. The inoculation of myotoxin in gastrocnemius muscle of white mice produce liberation of creatin kinase as well as myonecrosis. The myotoxin has phospholipasic, anticoagulant and edematic activity, but not hemolytic activity.